Európai integráció, keleti bővítés és a magyar regionális politika - Horváth, Gyula (Tér és Társadalom, 1997)
The policies of the European Communities established for the adjustment of macroeconomic processes have been transformed as consequence of economic development and subsequent enlargement of the EC. The joining of the Mediterranean countries resulted in increasing regional differences from the 1980ies on. For this reason; the main purpose of the policy reforms was the acceleration of the integration process and strengthening the cohesion inside the Community. Major emphasis was put on regional development in terms of policies and financial funds. The latter was given a new framework by enhancing and reforming the Structural Funds. In the next phase of reforms, cohesion problems and expenses resulted by the eastern enlargement of the EU will be considered. In the future, only poorly performing areas and regions suffering from deficiencies of their economic structure or the inadequacy of labour resources may expect assistance from the EU. The new, eastern members for their general backwardness will absorb a substantial part of the available fmancial support. The centres of economic development are the capitals and regions of major cities in the Poland, the Czech Republic and Hungary. The losers of the transition period are rural regions and industrial districts having deficient economic basis. National governments will be the mediators of the EU assistance in diminishing spatial differences. The applicant countries have to face with the need for the adjustment of their regional policies, administration and institutions. Hungary is in the most advanced position in terms of legislative framework, its compatibility with the EU regulations and the establishment of institutions of the regional policy. The weaknesses of the Hungarian system are the lacking division of duties and competence among institutions that should be clarified; the unsettled form of the NUTS II level in regional planning, contradictions of the NUTS IV level and the ínsufficiency of the professional staff of regional development councils. In the future, reform of financial framework, formation of EU-compatible regions, transformation of recent mechanism of distribution, incorporation of regional policy into goverrimental economic policies and development of the institutional system must be implemented to preserve the favourable position of Hungary amongst the applicant countries.